Portal Hypertensive Polyps as Gastroscopic Finding in Liver Cirrhosis - Firdevs Topal; Sabiye Akbulut; Cengiz Karahanlı; Süleyman Günay; Elif Sarıtaş Yüksel; Fatih Esad Topal (Gastroenterology Research and Practice)
Background. Portal hypertensive polyps in patients with portal hypertension are described. Aims. The most significant and serious complication in liver cirrhosis proves to be portal hypertension. Polypoid lesions, which can be seen in the stomach as endoscopic finding in patients with portal hypertension, have not quite been defined in the literature. The aim of this study, therefore, was to define polypoid lesion formation due to portal hypertension in the upper gastrointestinal system in patients with portal hypertension. Study Design. Cross-sectional study. Methods. The study covered a group of patients with liver cirrhosis and a healthy control group that did not have portal hypertension. All individuals covered by the study received upper GI endoscopy, while the endoscopic features and pathological characteristics of the identified polypoid lesions were defined. Standard histological criteria were used in polyp diagnosis. Results. A total of 400 individuals were included in the study. Upper GI endoscopy was performed for 200 patients with liver cirrhosis and another 200 healthy individuals with no portal hypertension in the control group. When the cases were gastroscopically assessed with regard to polypoid lesion presence, it was seen that a total of 87 (21.8%) individuals had polyps. While 67 (33.5%) cirrhotic patients were identified to have polyps, 20 (10%) individuals in the healthy control group had polyps. When the results of those with liver cirrhosis who received esophageal variceal endoscopic band ligation (EVL) and who did not were compared, it was observed that a higher number of individuals in the group with EVL had polypoid lesions. When the patient and control groups were compared as to Helicobacter pylori presence, the results showed that it was slightly higher in the dyspepsia group but the difference was not statistically significant (p>0.05). Conclusion. Portal hypertension-associated polypoid lesions are common in advanced liver cirrhosis cases. The pathological analyses of these polyps pointed out that they were all benign and no malignant cases were detected. It was argued that these polypoid lesions, referred to as portal hypertensive polyps, were associated with elevated angiogenesis in the gastric mucosa.